Utilisation de Trifolium tembense pour completer les rations des ruminants a base de residus agricoles - Mosi, A.K.; Butterworth, M.H. (1983)
Deals with an experiment on the use of legume to enhance crop residue utilization by ruminants; includes in the study - hay from Trifolium tembense, 20 Ethiopian highland sheep, and teff & wheat straw, oat hay and maize stover.